2016
DOI: 10.1038/srep26445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise and Calorie Restriction on Tissue Acylcarnitines, Tissue Desaturase Indices, and Fat Accumulation in Diet-Induced Obese Rats

Abstract: Both exercise and calorie restriction interventions have been recommended for inducing weight-loss in obese states. However, there is conflicting evidence on their relative benefits for metabolic health and insulin sensitivity. This study seeks to evaluate the differential effects of the two interventions on fat mobilization, fat metabolism, and insulin sensitivity in diet-induced obese animal models. After 4 months of ad libitum high fat diet feeding, 35 male Fischer F344 rats were grouped (n = 7 per cohort) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…Data on protein acetylation under CR from our study and two other studies (Sato et al, 2017; Schwer et al, 2009) are in line with the increase in acetyl‐CoA in CR liver. Gopalan et al also reported an induction for a few long‐chain acylcarnitines; however, the effect was significant for 15% CR but not 30% CR (Gopalan et al, 2016). To the best of our knowledge, the effect of CR on acylcarnitine profile in healthy animals has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Data on protein acetylation under CR from our study and two other studies (Sato et al, 2017; Schwer et al, 2009) are in line with the increase in acetyl‐CoA in CR liver. Gopalan et al also reported an induction for a few long‐chain acylcarnitines; however, the effect was significant for 15% CR but not 30% CR (Gopalan et al, 2016). To the best of our knowledge, the effect of CR on acylcarnitine profile in healthy animals has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological significance of ACs is complex, since, as stated in the Introduction, increased levels in plasma and tissues are observed in obesity and insulin resistant state [25,26,27,28,29], but also after weight loss and exercise [30,31,32]. It appears that, depending on the conditions, excess ACs may inflict insulin resistance or simply reflect FAO rates in tissues [24].…”
Section: Discussionmentioning
confidence: 99%
“…Further, AC synthesis and efflux from mitochondria serves physiological functions in the modulation of cellular metabolism, as it helps avoiding both the sequestration of mitochondrial CoA in the form of acyl-CoAs and the feed-back inhibition of the pyruvate dehydrogenase complex (and hence of glucose oxidation) by excess mitochondrial acetyl-CoA [24,51]. Interestingly, increments in long-chain AC levels found under conditions of obesity, high-fat diet, or lipid stress take place in parallel with decreased tissue and plasma levels of free carnitine [52,53], whereas increments of AC levels found under conditions of weight loss or exercise take place in parallel with increases in the tissue/ plasma levels of free carnitine [30,32]. In fact, carnitine insufficiency is a common feature of insulin-resistant states such as advanced age and diet-induced obesity in rodents [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, controlling these factors could effect on the development of obesity and longevity. Several evidence indicates that caloric restriction (CR) can reduce bodyweight (Das et al 2017;Gopalan et al 2016) and enhance longevity (Holloszy and Fontana 2007;Lane et al 1997;Martin-Montalvo et al 2013;Mattison et al 2017;Ravussin et al 2015;Verdery et al 1997). In monkeys, a 30% reduction of caloric intake leads to a significantly elevated level of a good cholesterol (HDL 2B) and a decreased level of triglyceride which further reduce risk for agingrelated disorders such as cardiovascular disease (Verdery et al 1997).…”
Section: Introductionmentioning
confidence: 99%